IN-VITRO ANTICOAGULANT EFFECT OF AERIAL PARTS EXTRACTS OF YEMENI FAGONIA SCHWEINFURTHII HADIDI - Alhaj, Hend Ahmed; Raweh, Salwa M.; Al-Kaf, Ali Gamal; Ibrahim, Hassan M. (Universal Journal of Pharmaceutical Research, 2022)
Background: Blood coagulation is a quick and effective process that results in the creation of clots, which demands to monitor. Many illness disorders include an abnormality in blood coagulation. This study examined the in vitro effects of methanol, ethyl acetate, and n-hexane extracts from aerial parts of Fagonia schweinfurthii Hadidi on healthy human volunteers’ blood coagulation. Methods: The Secondary metabolites were extracted from dried and crushed F. schweinfurthii aerial parts using n-hexane, ethyl acetate, and methanol, respectively. Additionally, the extracts were tested in vitro at different concentrations (10-100 µg/ml) on the blood coagulation profile, prothrombin time (PT), and activated partial thromboplastin time (a PTT) of apparently healthy human volunteers. Results: Methanol, ethyl acetate, and n-hexane extracts of F. schweinfurthii aerial parts significantly (p˃0.05) prolonged PT and PTT in the blood of healthy human volunteers with Ethyl acetate and methanol extracts recorded the largest prolongation of PT and PTT correspondingly. The highest PT and PTT prolongation was achieved at 100µg/ml, and the least prolongation time was obtained at 10µg/ml. Conclusion: These findings displayed that F. schweinfurthii aerial parts contain phytochemical constituents with anticoagulant characteristics and could be used to treat blood clotting disorders. Peer Review History: Received: 2 April 2022; Revised: 12 May; Accepted: 14 June; Available online: 15 July 2022 Academic Editor: Dr. DANIYAN Oluwatoyin Michael , Obafemi Awolowo University, ILE-IFE, Nigeria, toyinpharm@gmail.com Reviewers: Dr. Gehan Fawzy Abdel Raoof Kandeel, Pharmacognosy Department, National Research Centre, Dokki, 12622, Giza, Egypt, gehankandeel9@yahoo.com Dr. Marwa A. A. Fayed, University of Sadat City, Egypt, maafayed@gmail.com Prof. Dr. Hüsniye Kayalar, Ege University, Turkey, husniyekayalar@gmail.com